Influence of the diet on in situ disappearance of dry matter, organic matter, and neutral detergent fiber of hydrolysed sugar cane bagasse - Borges, I.; Gonçalves, L. C.; Morais, M. G.; Zeoula, L. M.; Franco, G. L. [UNESP] (FapUNIFESP (SciELO), 2000)
The effects of two diets based on hydrolysed sugarcane bagasse (HSB) and whole cottonseed (WCS), with or without oat hay, were analyzed for the in situ disappearance of dry matter (DM), organic matter (OM) and neutral detergent fiber (NDF) of HSB. Six mature castrated rams with a permanent T ruminai cannula were used in a complete randomized split plot design. The incubation times were 3, 6, 9, 12, 24, 48 and 72h. The diet with oat hay showed higher disappearance indexes for the NDF fraction. Furthermore, the maximum degradation of HSB constituents was reached around 48h of incubation. The diets were T1=64% hydrolyzed sugarcane + 36% whole cottonseed and T2=14% hydrolyzed sugarcane bagasse + 36% cottonseed + 50% oat hay.
Influência da dieta sobre o desaparecimento in situ da matéria seca, da matéria orgânica e da fibra em detergente neutro do bagaço de cana-de-açúcar auto-hidrolisado
Keywords: Hydrolysed bagasse; In situ degradability; NDF; Sheep; Sugar cane